The Effect of Using Problem Based Chemical Module Assisted by the Quartchem Card on Students Learning Outcomes and Creativity - Ningtyas, Yanuar Ayu; Haryani, Sri; Mursiti, Sri (Universitas Negeri Semarang)
Following education in the 21st century, students must to having a lot of skills one of them is creativity. Fresh graduates of vocational high school required to have high creativity. Low students creativity being a problem that must be faced by the teacher. This study aims to find the effect of the problem-based chemistry module with the help of Quartchem cards on student learning outcomes and student achievement in chemistry learning on the subject of chemical bonding. Grade X motorcycle engineering which consist of three class used for population of this research. The sampling technique was carried out by cluster random sampling with class X TSM 3 as the experimental class and class X TSM 2 as the control class. Data collection was carried out by three methods, there are documentation method, test method, and observasion sheets method. The test method is used to measure students 'cognitive learning outcomes using the pre-test and post-test question instruments, while the observation sheet method is used to measure students' creativity using the student's creative product observation sheet. The test method is used to measure students 'cognitive learning outcomes using the pre-test and post-test question instruments, while the observation sheet method is used to measure students' creativity using the student's creative product observation sheet. The results showed that the experimental class learning outcomes average was 86.20 and the control class was 81.96 while the average creativity of the experimental class was 84.379 and the control class was 72.3. The results of data analysis with the t-test of the right side for student learning outcomes obtained tcount 2.212 and for creativity obtained tcount 11.94 with t table 1.67 shows that there is an effect of problem-based chemistry modules assisted by Quartchem cards on student learning outcomes and creativity.